Combined effect and mechanism of visible light and Ag+ on chalcopyrite bioleaching. (1st January 2022) - Zhao, Chunxiao; Yang, Baojun; Liao, Rui; Hong, Maoxin; Yu, Shichao; Liu, Shitong; Wang, Jun; Qiu, Guanzhou
Graphical abstract: Highlights: Visible light and Ag + have synergistic catalytic effect on chalcopyrite bioleaching. Ag + introduced Ag2 S and Ag 0 on the surface of chalcopyrite. Light illumination promoted the formation of Ag2 S and Ag 0 on chalcopyrite surface. The formation of covellite-like species hindered the dissolution of chalcopyrite. Ag + and visible light reduced the resistance of the passivation layer. Abstract: The effect and mechanism of visible light and Ag + on chalcopyrite bioleaching were investigated in the presence of Acidithiobacillus ferrooxidans . The results of bioleaching tests revealed that the copper extraction was improved significantly when visible light and Ag + were simultaneously present. By analyzing bioleaching parameters, scanning electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy results: the accumulation of jarosite and the formation of covellite-like species led to the slow dissolution rate of chalcopyrite at the end period of bioleaching. The introduction of Ag + resulted in the formation of Ag2 S and Ag 0 on the surface of chalcopyrite. And light illumination promoted the accumulation of Ag2 S and Ag 0 on chalcopyrite surface, thus reducing the resistance of the passivation layer. Further, light illumination increased the rate of charge transfer and promoted the dissolution of chalcopyrite.